Determinants of organic food consumption. A systematic literature review on motives and barriers. (1st December 2019) - Kushwah, Shiksha; Dhir, Amandeep; Sagar, Mahim; Gupta, Bhumika
Abstract: During the last few decades, interest in organically produced food has steadily risen around the world. Consequently, academic interest in better understanding the different motives and barriers underlying organic food consumption has also increased. But, the scope of these published studies is both broad and fragmented. There is a lack of research that systematically examines and presents a comprehensive review of the different motives and barriers and their association with purchase decisions. The current study shows a systematic literature review of different motives and barriers and their association with purchase decisions in context to organic food. A total of 89 empirical studies was considered in the review. Two popular theoretical frameworks, namely the theory of consumption values and innovation resistance theory, were used to categorize the identified motives and barriers. The primary outcomes of this systematic literature review are: a) descriptive statistics on the selected studies; b) comprehensive summary of motives and barriers mentioned in selected studies using theory of consumption values and innovation resistance theory; c) classification of motives and barriers on consumer involvement, research design and country status; d) framework on the association between motives, barriers and purchase decisions; e) implications for scholars, managers, and policymakers interested in better understanding issues related to organic food consumption.